2017
DOI: 10.1371/journal.pone.0181133
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoid-induced leucine zipper (GILZ) in inflammatory bone loss

Abstract: TNF-α plays a key role in the development of rheumatoid arthritis (RA) and inflammatory bone loss. Unfortunately, treatment of RA with anti-inflammatory glucocorticoids (GCs) also causes bone loss resulting in osteoporosis. Our previous studies showed that overexpression of glucocorticoid-induced leucine zipper (GILZ), a mediator of GC’s anti-inflammatory effect, can enhance osteogenic differentiation in vitro and bone acquisition in vivo. To investigate whether GILZ could antagonize TNF-α-induced arthritic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This search has led to the discovery of the glucocorticoid-induced leucine zipper (GILZ) protein, a member of the TSC-22D family with remarkable similarity in amino acid sequence between human and mouse, as a very predictive and responsive target of glucocorticoids and mediator of their anti-inflammatory effects (D'Adamio et al, 1997;Riccardi et al, 1999;Cannarile et al, 2001;Ayroldi and Riccardi, 2009;Fan and Morand, 2012;Bereshchenko et al, 2014;Ronchetti et al, 2015). Consequently, GILZ is shown to beneficially impact several conditions associated with dysregulation of immune and inflammatory responses including myocardial infarction (Cannarile et al, 2009;Beaulieu et al, 2010;Fan and Morand, 2012;Jones et al, 2015;Baban et al, 2017;Srinivasan and Lahiri, 2017;Yang et al, 2017). However, the impact of GILZ on pathologies involving the kidney remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…This search has led to the discovery of the glucocorticoid-induced leucine zipper (GILZ) protein, a member of the TSC-22D family with remarkable similarity in amino acid sequence between human and mouse, as a very predictive and responsive target of glucocorticoids and mediator of their anti-inflammatory effects (D'Adamio et al, 1997;Riccardi et al, 1999;Cannarile et al, 2001;Ayroldi and Riccardi, 2009;Fan and Morand, 2012;Bereshchenko et al, 2014;Ronchetti et al, 2015). Consequently, GILZ is shown to beneficially impact several conditions associated with dysregulation of immune and inflammatory responses including myocardial infarction (Cannarile et al, 2009;Beaulieu et al, 2010;Fan and Morand, 2012;Jones et al, 2015;Baban et al, 2017;Srinivasan and Lahiri, 2017;Yang et al, 2017). However, the impact of GILZ on pathologies involving the kidney remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that GILZ is lacking during chronic inflammation and the inflammation arising from trauma [17,18], and that it exerts anti-inflammatory and immunosuppressive effects in these diseases. The biological activity of a full-length GILZ fusion protein has previously been described [19][20][21][22]. Our previous studies have found that full-length GILZ suppressed ICAM-1 and MCP-1 expression by dephosphorylating NF-κB p65 in retinal endothelial cells in vitro [23] and inhibited LPSinduced retinal inflammation in rats in vivo [10].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, they also negatively affected basal GR activity when applied individually, with LY294002 being the most effective. Attenuation of GR TA was further confirmed by Q-PCR analysis of known GR-target genes including GR chaperone FKBP51 (12,14), mediator of Gcs anti-inflammatory effects GILZ (22,23), transcriptional activator KLF9 (24), and inhibitor of cytokine production MKP-1 (ref. 25; Fig.…”
Section: Pi3k Inhibitors Decreased Gr Phosphorylation and Nuclear Translocation And Shifted Gr Function Toward Trmentioning
confidence: 82%